Identification of Factors Influencing Health Workers' Resistance to Patient Safety Culture at Hospital X Surabaya - Edho Yulianto Suwardi; Nyoman Anita Damayanti (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2026)
Implementing patient safety culture is essential to ensuring the accuracy and quality of healthcare services in hospitals. When not effectively enforced, a deficiency in safety culture can lead to significant adverse outcomes not only for patients but also for healthcare workers and the institutions involved. Data from Hospital X in Surabaya indicated that 56 patient safety incidents were reported in 2024, including 23 near-miss incidents, 28 non-injury incidents, and 5 unexpected incidents. This study aims to identify the factors influencing health workers' resistance to patient safety culture at Hospital X in Surabaya through a survey. A quantitative research design employing a cross-sectional approach was employed, with data collected from 267 respondents and analyzed using linear regression. The hospital's implementation of patient safety culture was perceived to be inadequate in several areas: (1) Shift Handover and Information Exchange; (2) Disclosure of Information; (3) Staff Arrangement and Work Rhythm; (4) Response to Errors; and (5) Patient Safety Event Reporting. Conversely, the aspects perceived positively included: (1) Support for Health Service Facilities; (2) Teamwork; (3) Direct Supervisor Support; (4) Communication Errors; and (5) Organizational Learning and Continuous Improvement. One significant factor identified as influencing this outcome is the use of patient safety reporting as a means of organizational learning (p-value 0.02). Enhancing organizational learning, despite perceptions of favorable aspects, could reduce staff resistance to adopting a more robust patient safety culture.  Keywords: Patient safety culture, health worker, resistance